Effect of the Medical City Waste on the Non-Diatom Planktonic Algae in the Tigris River in Central Baghdad - Abd Al-Aziz Hasan Al-Mgadamy , Buthena; Manar Nidal Oda (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
We conducted a study on the quality of non-diatom planktonic algae in the Tigris River during the autumn 2022 and winter 2023 seasons. The study focused on the impact of the medical city waste discharge to the Tigris River at three sites: Al-Sarafiya Bridge in the north, Medical City, and the Bab Al-Mu'adam Bridge in the south of Khader Elias. The study also examined some physical and chemical variables of the river water. Findings showed that there are 74 species (38 genera) of non-diatom algae in four orders. The blue-green algae Cyanophyceae and Chlorophyceae had the most species, with 35 species belonging to 19 genera and 16 genera per division, or 47% of all algae. Euglenophyceae had 5%, with 3 species and 2 genera, and Chrysophyceae had only one species and a genus, making up 2% of all algae species. The study demonstrated that liquid waste had an impact on river water, leading to a rise in nutrient concentration, the emergence of new pollution-tolerant planktonic algae species, and an increase in diversity within the Medical City site, with the effect extending beyond its boundaries.